Reliability of running economy measurements: Influence of shoe familiarisation - Nielsen, A.; Heyde, C.; Simonsen, M. B.; Larsen, R. G.; Hansen, R. K.; Kersting, U.; De Zee, M.; Korsgaard Brund, R. (International Journal of Sports Medicine, 2022)
The purpose was to investigate differences in reliability of running economy measurements between familiar and unfamiliar shoes. Thirty-seven runners were included who all ran in familiar and unfamiliar running shoes while running economy was measured at steady state using a treadmill. Each participant was tested on two different visits (three sessions in total), with two trials in each of the three shoe conditions completed at each visit. Coefficient of variation, standard deviation of differences, and limits of agreement of running economy were used to quantify the repeatability (within-visit variation) and reproducibility (between-visit variation). The coefficient of variation showed a marginal difference in reproducibility across shoe conditions, whereas no differences were seen in coefficient of variation, standard deviation of the differences, or limits of agreement for repeatability across shoes. All three shoe conditions showed greater repeatability than reproducibility for running economy, and enhanced repeatability at visit 3 compared to visit 2. Our results indicate that familiarisation to shoes might not be needed for reliable measurements of running economy. Based on our results, when evaluating benefits in running shoes we suggest that running economy be assessed within the same day. Further, our data suggest a beneficial effect of using multiple familiarisation sessions if small differences between shoe conditions are expected.